The Role of Teacher Support, Self-Efficacy, and Academic Emotions in Predicting Primary School Students Learning Performance Within a Formative Assessment Model - Nonih Nur Syah Lukiyah; Hilyah Auliya; Khilda Tamami (LEOTECH: Journal of Learning Education and Technology, 2025)
This study investigates the influence of teacher support, academic self-efficacy, and academic emotions on the learning performance of elementary school students through the development of a formative assessment model. A supportive classroom environment is essential for fostering student motivation, emotional regulation, and optimal academic achievement. The study involved 240 students from public elementary schools in Cirebon, Indonesia, using a structured quantitative survey. Research instruments measured teacher support, academic self-efficacy, academic emotions, and student performance. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), a variance-based structural equation modeling approach, with SmartPLS 3.0 software. Results show that teacher support has a strong direct effect on learning performance (β = 0.845; f² = 2.524), and also exerts indirect effects through positive academic emotions (β = 0.134) and academic self-efficacy (β = -0.034). The structural model explains 75.9% of the variance in student performance (R² = 0.759). These findings emphasize the critical role of teacher support and students’ psychological factors in formative assessment, suggesting that integrating socio-emotional variables can improve learning effectiveness in primary education.